2018
DOI: 10.1038/s41467-018-07261-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal single-cell RNA sequencing of patient-derived primary cells reveals drug-induced infidelity in stem cell hierarchy

Abstract: Chemo-resistance is one of the major causes of cancer-related deaths. Here we used single-cell transcriptomics to investigate divergent modes of chemo-resistance in tumor cells. We observed that higher degree of phenotypic intra-tumor heterogeneity (ITH) favors selection of pre-existing drug-resistant cells, whereas phenotypically homogeneous cells engage covert epigenetic mechanisms to trans-differentiate under drug-selection. This adaptation was driven by selection-induced gain of H3K27ac marks on bivalently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
140
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(160 citation statements)
references
References 45 publications
19
140
1
Order By: Relevance
“…Human cell lines are a mainstay of cancer research and drug discovery, yet our current knowledge of their ability to recapitulate the expression diversity observed in patient samples is limited. Only a few cancer cell lines have been comprehensively profiled by scRNA-seq so far (Ben-David et al, 2018;Jerby-Arnon et al, 2018;Kim et al, 2015;Sharma et al, 2018). Thus, models are often chosen based on their mutational status, historical popularity, and ease of culturing.…”
Section: Introductionmentioning
confidence: 99%
“…Human cell lines are a mainstay of cancer research and drug discovery, yet our current knowledge of their ability to recapitulate the expression diversity observed in patient samples is limited. Only a few cancer cell lines have been comprehensively profiled by scRNA-seq so far (Ben-David et al, 2018;Jerby-Arnon et al, 2018;Kim et al, 2015;Sharma et al, 2018). Thus, models are often chosen based on their mutational status, historical popularity, and ease of culturing.…”
Section: Introductionmentioning
confidence: 99%
“…Our approaches are likely beneficial to characterizing SCCN data derived from single-cell RNA sequencing (scRNA-seq) experiments. To examine that possibility, we collected data obtained from paired primary and metastasis (or relapse) samples of a variety of cancer patients, including 6 head and neck squamous cell carcinoma (HNSCC) 20 , 8 multiple myeloma (MM), 2 oral squamous cell carcinomas (OSCC) 45 and 4 ovarian cancer patients (OV) 46 ( Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…We generated Patient derived cell lines (PDCs) for each patient from lymph node metastatic sites (HN120m, HN137m). We recently demonstrated that these cells all present very distinct genomic profiles 16,17 . They also displayed inherent heterogeneity in migration potential and Epithelial to Mesenchymal transition (EMT) scores 18 .…”
Section: Migratory Sorting Of Metastatic Cells and Correlation With Ementioning
confidence: 99%